Charge transfer drives anomalous phase transition in ceria. Issue 1 (December 2018) - Zhu, He; Yang, Chao; Li, Qiang; Ren, Yang; Neuefeind, Joerg; Gu, Lin; Liu, Huibiao; Fan, Longlong; Chen, Jun; Deng, Jinxia; Wang, Na; Hong, Jiawang; et al.
Abstract Ceria has conventionally been thought to have a cubic fluorite structure with stable geometric and electronic properties over a wide temperature range. Here we report a reversible tetragonal (P 42 /nmc ) to cubic (Fm -3m ) phase transition in nanosized ceria, which triggers negative thermal expansion in the temperature range of −25 °C–75 °C. Local structure investigations using neutron pair distribution function and Raman scatterings reveal that the tetragonal phase involves a continuous displacement of O2− anions along the fourfold axis, while the first-principles calculations clearly show oxygen vacancies play a pivotal role in stabilizing the tetragonal ceria. Further experiments provide evidence of a charge transfer between oxygen vacancies and4f orbitals in ceria, which is inferred to be the mechanism behind this anomalous phase transition. Nanosized ceria has conventionally been thought to have a cubic fluorite structure. Here, the authors use a combination of experiments and simulations to show that oxygen vacancies in ceria promote a charge-transfer induced phase transition from tetragonal to cubic.